2017
DOI: 10.1016/j.neo.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Specific microRNA–mRNA Regulatory Network of Colon Cancer Invasion Mediated by Tissue Kallikrein–Related Peptidase 6

Abstract: Metastatic colon cancer is a major cause of deaths among colorectal cancer (CRC) patients. Elevated expression of kallikrein 6 (KLK6), a member of a kallikrein subfamily of peptidase S1 family serine proteases, has been reported in CRC and is associated with low patient survival rates and poor disease prognosis. We knocked down KLK6 expression in HCT116 colon cancer cells to determine the significance of KLK6 expression for metastatic dissemination and to identify the KLK6-associated microRNAs (miRNAs) signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 51 publications
2
36
0
1
Order By: Relevance
“…HCT116 colon cancer cells with knockdown of KLK6 expression (shKLK6 cells) were generated by stable transfection of SureSilencing shRNA plasmids (SureSilencing shRNAs, QIAGEN, Inc.), targeting the KLK6 gene using short-hairpin RNA (Fig. S2) [16]. Cell growth conditions are listed in the ESM.…”
Section: Methodsmentioning
confidence: 99%
“…HCT116 colon cancer cells with knockdown of KLK6 expression (shKLK6 cells) were generated by stable transfection of SureSilencing shRNA plasmids (SureSilencing shRNAs, QIAGEN, Inc.), targeting the KLK6 gene using short-hairpin RNA (Fig. S2) [16]. Cell growth conditions are listed in the ESM.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that knockdown of KLK6 reduces migration and invasion of HCT116 cells in vitro. [13] In order to test whether this effect could be recapitulated with small molecule KLK6 inhibitors, we measured the ability of 32 to reduce invasion of HCT116 cells. Because the enantiomer of 32 was never prepared, compound 9, the enantiomer of hit 5, was used as an inactive control substance.…”
Section: Lead Compound Pharmacokinetic Propertiesmentioning
confidence: 99%
“…[12] KLK6-promoted migration was also observed in colon cancer, where knockdown of KLK6 reduced migration and invasion of HCT116 cells in vitro. [13] Furthermore, in an orthotopic colon cancer mouse model, mice injected with KLK6 positive HCT116 cells had significantly more metastases and worse survival than mice injected with shKLK6 HCT116 clones. [13] Nevertheless, the role of KLK6 needs further investigation in these and other types of cancers, as its role is clearly tumordependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, as Zheng et al 125 suggest, ING5 is up regulated at cytoplasmic level in colorectal cancer cases. MNS1 (meiosis specific nuclear structural 1) was found to be down regulated via knockdown of KLK6 127 . KLK6 is observed to be highly regulated in colorectal cancer cases and facilitates in the invasion-metastasis formation via specific downstream network of miRNA-mRNA effectors.…”
Section: Dicationmentioning
confidence: 99%